One Hundred Years On: Have Prisons Switched from Deterrence to Reform?. (11th October 2021) - DHANUKA, MADHURIMA
Abstract: Today over 1.5 million people are imprisoned in Commonwealth countries and the average occupancy level is 129%. The rise in prison populations is often attributed to the existence of punitive systems that have failed to fulfil the rehabilitative purpose of imprisonment. This article sets forth pertinent data on prisons in the Commonwealth nations, which have evolved from common colonial histories and traditions, to highlight perennial problems within the system. To further illustrate these concerns, it delves into a reflection from the findings of the Report of the Indian Jails Committee, 1919–20, and the Indian prison system of today. In doing this, the article encapsulates the journey of reforms implemented in the last 100 years in India.